1984
DOI: 10.1002/art.1780270305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a partially purified fraction of an ant venom in rheumatoid arthritis

Abstract: A partially purified extract of an ant venom from the South American tree ant Pseudomyrmex sp. was tested in a double-blind, controlled study of patients with rheumatoid arthritis. Venom treated patients demonstrated an improvement in global efficacy and a decrease in the number of tendedpainful joints and swollen joints. Swollen joint index improved in 60% of venom treated patients. Other parameters did not demonstrate significant change. Reduction of joint swelling was followed by symptomatic improvement tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The present study is in accordance with the literature that show antinociceptive and antiinflammatory activities of other Hymenoptera venoms, such as bee venom constituents (Bogdan, 2001;Lee & Bae, 2016) and ant venoms (Yoon et al, 2015;Altman et al, 1984), including those of D. quadriceps (Sousa et al, 2012). In this line, the novel data concerning the antiinflammatory and antinociceptive effects of DqV on traumatic wounds in mice open new and better possibilities for wound care.…”
Section: Resultssupporting
confidence: 92%
“…The present study is in accordance with the literature that show antinociceptive and antiinflammatory activities of other Hymenoptera venoms, such as bee venom constituents (Bogdan, 2001;Lee & Bae, 2016) and ant venoms (Yoon et al, 2015;Altman et al, 1984), including those of D. quadriceps (Sousa et al, 2012). In this line, the novel data concerning the antiinflammatory and antinociceptive effects of DqV on traumatic wounds in mice open new and better possibilities for wound care.…”
Section: Resultssupporting
confidence: 92%
“…In vitro and clinical studies have shown that Pseudomyrmex triplarinus (Pseudomyrmecinae) ant venom decreases pain and inflammation in patients with rheumatoid arthritis and reduces swelling in animal models of inflammation (Altman et al, 1984;Hink and Butz, 1985;Schultz and Arnold, 1984). Myrmexins are a family of six related polypeptides (myrmexins IeVI) that have been purified from the venom of Pseudomyrmex triplarinus.…”
Section: Myrmexinsmentioning
confidence: 97%
“…Among the more noticeable of these chemicals are their venoms, which they use for defense, food acquisition, and communication (Schmidt, 1982;Hölldobler and Wilson, 1990). Studies of ant venoms have shown them to be both chemically and pharmacologically diverse (Schmidt, 1986;Blum, 1988;Piek et al, 1991;Zelezetsky et al, 2005;Hoffman, 2010), as well as potentially medically useful (Altman et al, 1984;Piek et al, 1991;Zelezetsky et al, 2005;Dkhil et al, 2010;Badr et al, 2012). Though the chemical properties and activities of ant venoms have been addressed in many studies, basic venom-related physiological questions have received less attention.…”
Section: Introductionmentioning
confidence: 97%